Pengaruh Latar Belakang Keuangan terhadap Keputusan Investasi Generasi Y di Kota Palembang - Nabila Firda; Isni Andriana; Mu’izzudin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to analyze the impact of financial background on investment decisions-making among Generation Y in Palembang. The population in this study are Generation Y, namely those born between 1980 and 1995 or aged between 25 and 40 in Palembang. Which sampling method in this study is using the Purposive Sampling method with 142 respondents as samples. This research uses quantitative methods with primary data sources obtained from distributing questionnaires to respondents. Data were analyzed using Multiple Linear Regression Analysis. The result showed that the demographic factors such as age, education, and occupation has no significant effect on investment decisions, meanwhile social environment and financial literacy has a significant effect on investment decisions among Generation Y in Palembang.